Evaluation of Voice Handicap and Emotional Status among Dysphonic and Non-Dysphonic Individuals A Cross-Sectional Survey - Auwal Adamu (Amrita Journal of Medicine)
Background: Dysphonia impairs verbal communication of the sufferer, which can lead to social isolation, depression, and reduced quality of life. Evaluation of voice handicap and emotional impact of dysphonia are not routinely consider in our laryngology and voice clinics, despite the fact that about 50% to 60% of patients with dysphonia have social and psychological problems.